Toward Identification of the Sexual Killer: A Comparison of Sexual Killers Engaging in Post-Mortem Sexual Interference and Non-Homicide Sexual Aggressors. (August 2017) - Higgs, Tamsin; Carter, Adam J.; Stefanska, Ewa B.; Glorney, Emily
Establishing a model of sexual assault reflecting psychosocial and behavioral characteristics of perpetrators of sexual killing and rape is necessary for development in risk assessment and intervention. Methodological variations in defining sexual killing have amalgamated serial and non-serial offenders and perpetrators with direct and indirect associations between killing and sexual arousal. This study defined sexual killing specifying that killing should be directly linked to sexual arousal, and sampled 48 sexual killers, operationalized to include only those engaging in post-mortem sexual interference, with one or two known female victims (non-serial), from prison service national (England and Wales) databases. These sexual killers were compared with 48 non-homicide, life or indeterminately sentenced sexual aggressors on psychological and crime scene characteristics. Contrary to previous research, fatal outcomes were associated with neither stranger victims nor weapon presence; sexual killing was characterized by severity of violence less so than non-fatal assault. Sexual killers more often reported problems with emotional loneliness, empathic concern, and sexual entitlement than the sexual aggressors. Theoretical and applied implications are discussed.